Nickel‒cobalt bimetallic catalysts prepared from hydrotalcite-like compounds for dry reforming of methane. (8th July 2022) - Duan, Xiaoxuan; Pan, Jinhua; Yang, Xinru; Wan, Chunsheng; Lin, Xingyi; Li, Dalin; Jiang, Lilong
Abstract: Ni–Co/Mg(Al)O alloy catalysts with different Co/Ni molar ratios have been prepared from Ni- and Co-substituted Mg–Al hydrotalcite-like compounds (HTlcs) as precursors and tested for dry reforming of methane. The XRD characterization shows that Ni–Co–Mg–Al HTlcs are decomposed by calcination into Mg(Ni, Co, Al)O solid solution, and by reduction finely dispersed alloy particles are formed. H2 -TPR indicates a strong interaction between nickel/cobalt oxides and magnesia, and the presence of cobalt in Mg(Ni, Co, Al)O enhances the metal-support interaction. STEM-EDX analysis reveals that nickel and cobalt cations are homogeneously distributed in the HTlcs precursor and in the derived solid solution, and by reduction the resulting Ni–Co alloy particles are composition-uniform. The Ni–Co/Mg(Al)O alloy catalysts exhibit relatively high activity and stability at severe conditions, i.e., a medium temperature of 600 °C and a high space velocity of 120000 mL g −1 h −1 . In comparison to monometallic Ni catalyst, Ni–Co alloying effectively inhibits methane decomposition and coke deposition, leading to a marked enhancement of catalytic stability. From CO2 -TPD and TPSR, it is suggested that alloying Ni with Co favors the CO2 adsorption/activation and promotes the elimination of carbon species, thus improving the coke resistance. Furthermore, a high and stable activity with low coking is demonstrated at 750 °C. The hydrotalcite-derived Ni–Co/Mg(Al)O catalysts show better catalytic performance than many of the reported Ni–Co catalysts, which can be attributed to the formation of Ni–Co alloy with uniform composition, proper size, and strong metal-support interaction as well as the presence of basic Mg(Al)O as support. Graphical abstract: Image 1 Highlights: Composition-uniform Ni–Co alloy particles are generated from Ni–Co–Mg–Al HTlcs. HTlcs decompose to Mg(Ni, Co, Al)O that provides strong metal-support interaction. Ni–Co/Mg(Al)O alloy catalysts shows high activity and stability at 600 °C. Ni–Co alloying inhibits methane decomposition and coke deposition. Ni–Co alloying promotes the CO2 adsorption and the elimination of carbon species.